Seroprevalence of Treponema pallidum infection in Brazilian indigenous people: a cross-sectional study - Marcelo S. Barbosa; Júlio Henrique F. S. Queiroz; Erica C. S. Schnaufer; Gerlaine D. Silva; Michele F. R. Marques; Tiago S. Ferreira; Gleyce H. A. de Souza; Crhistinne C. M. Gonçalves; Silvana B. Marchioro; Simone Simionatto (Scientific Reports, 2024)
Abstract Indigenous communities in Brazil have a complex epidemiological profile, which increases their chances of contracting sexually transmitted diseases. However, limited data is available on Treponema pallidum infections in this population. We investigated the seroprevalence and risk factors associated with T. pallidum infection in an indigenous population of Dourados, Mato Grosso do Sul. Blood samples were collected from September 2017 to March 2020, and the participants were interviewed to obtain comprehensive data on demography and sexual behavior. Serological tests were performed to detect T. pallidum infection. Besides conducting descriptive analysis, we performed Chi-squared tests and determined the bivariate odds ratio. The data were also analyzed using logistic regression. Among the 2190 invited individuals, 1927 (88%) were included in this study. The seroprevalence of T. pallidum infection was 2.91%. The results of a multivariate analysis showed that individuals who were 30–39 years old, with up to 4 years of school education, living in households without piped water, with a history of genital lesions, multiple sexual partners, and having a history of STIs had the highest seroprevalence of T. pallidum. This study showed that behavioral, social, and economic factors play an important role in the transmission of T. pallidum within the indigenous population. Thus, targeted intervention, including imparting education in the native language, mass testing initiatives, and implementing public policies to improve socioeconomic indicators, is needed to reduce the cases of syphilis in this community.